REESTRUTURAÇÃO DOS ESPAÇOS DE APRENDIZAGEM NAS INSTITUIÇÕES DE ENSINO SUPERIOR: ANÁLISE QUALITATIVA DA CONTRIBUIÇÃO DA GESTÃO ESTRATÉGICA DO CONHECIMENTO - Martorelli, Bárbara Cristina Paulucci Cordeiro (2007)
This work presents a reflection developed in the inquiry of the contribution of the Management of Knowledge for reorganization of the pedagogical behavior in the education process and learning of the University. Theoretician is about a study eminently on the subject, with the objective to offer some tracks that enrich the debate on the ways to be followed in the education in this new century. The occurred transformations in the society in the last decades send them new educational paradigms to it in the Institutions of Superior Education. In view of the construction of possible answers to the presented problem, the inquiry procedure integrated the theoretical analysis to the analysis of the current reality. The work deals with as the society comes if developing since the industrial revolution, standing out the paradigms of the time and its influence in the process of educational management, until the revolution of the call "Age of the Knowledge", the emersion of a new paradigm and its conceptions. The abilities of the individual in this new context, the search of the individual and social identity in a society in constant movement, the reorganization of the spaces of learning in the University in set with the technological innovations and a holistic vision of the world and the individual in its relations are distinguished